IMPROVING THE STUDENT’S READING SKILL TROUGH SQ3R TECHNIQUE IN MTS AL-KHAIRIYAH - Widiawati, Titi; Nuraida, Ida; Saputri, Sisca Wulansari (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. The objectives of this research is to figure out whether or not the implementation of SQ3R technique can improve reading comprehension of the eighth grade students of Mts Al-Khairiyah in academic year 2018/2019. Therefore, to achieve the objective, the writer conducted a action research. This research was conducted in two cycles where each cycle had 2 sessions. The data were analyzed by comparing the result of pre-test and post-test. The result post- test showed the significant improvement. This research furthermore showed that most of the subjects gave positive response that SQ3R technique was successfully applied in improving the subjects’ reading comprehension. In conclusion, the present classroom action study proved that SQ3R technique could improve reading comprehension of the eighth grade students of Mts Al-Khairiyah in academic year 2018/2019.